The provenance of coarse-grained turbidite sandstones in the Kırkgeçit Formation (western part of the Elazığ Basin-east Turkey) - Alkaç, Onur; Aksoy, Ercan (TUBITAK, 2022)
Modal analysis of sandstones for conglomerate rich marine basins is useful for investigating the provenance types surrounded by plate tectonics. Different kinds of siliciclastic rocks are important indicators for defining the paleogeography and geotectonic conditions of the sedimentary basin by provenance analysis. This paper, which focuses on the petrography and provenance of conglomerate rich turbidite systems, is one of the rarest studies on the sedimentary characteristics in the scientific literature. In this context, the study was carried out in the western part of the Elazığ Basin. The Middle Eocene–Oligocene basin infill called the Kırkgeçit Formation is characterised by the conglomerate rich submarine channel deposits and coarse-grained turbidite sandstones. Petrographically, the coarse-grained sandstones of the Kırkgeçit Formation are composed of litharenite and rarely feldspathic litharenite, lithic arkose and rock fragments. Mostly the components are derived from volcanic and plutonic rocks of the Elazığ Magmatites. Fossils and fossil fragments are transported from the shallow part of the western Elazığ Basin. The components transported from metamorphic rock fragments, which are rarely observed in the sandstone samples, are composed of recrystallized limestones and derived from Keban Metamorphites in the northern part of the basin. The provenance studies and petrographic analyses indicated that the conglomerate rich channels and coarse-grained sediments of turbidite sandstones in the Kırkgeçit Formation were plotted mostly to the recycled orogenic and undissected arc type source rocks. Therefore, this type of source rocks has been reflected as a back-arc basin deposit during MiddleUpper Eocene. The geotectonic evolution of the western Elazığ Basin has also supported this remark. © TÜBİTAK.
Keywords: Coarse-grained turbidites; Elazığ Basin; Kırkgeçit Formation; Petrography; Provenance